Recognizing the tenascin‐X deficient type of Ehlers–Danlos syndrome: a cross‐sectional study in 17 patients. Issue 3 (4th November 2016) - Demirdas, S.; Dulfer, E.; Robert, L.; Kempers, M.; van Beek, D.; Micha, D.; van Engelen, B.G.; Hamel, B.; Schalkwijk, J.; Loeys, B.; Maugeri, A.; Voermans, N.C.
Abstract : The tenascin‐X (TNX) deficient type Ehlers–Danlos syndrome (EDS) is similar to the classical type of EDS. Because of the limited awareness among geneticists and the challenge of the molecular analysis of the TNXB gene, the TNX‐deficient type EDS is probably to be under diagnosed. We therefore performed an observational, cross‐sectional study. History and physical examination were performed. Results of serum TNX measurements were collected and mutation analysis was performed by a combination of next‐generation sequencing (NGS), Sanger sequencing and multiplex ligation‐dependent probe amplification (MLPA). Included were 17 patients of 11 families with autosomal recessive inheritance and childhood onset. All patients had hyperextensible skin without atrophic scarring. Hypermobility of the joints was observed in 16 of 17 patients. Deformities of the hands and feet were observed frequently. TNX serum level was tested and absent in 11 patients (seven families). Genetic testing was performed in all families; 12 different mutations were detected, most of which are suspected to lead to non‐sense mRNA mediated decay. In short, patients with the TNX‐deficient type EDS typically have generalized joint hypermobility, skin hyperextensibility and easy bruising. In contrast to the classical type, the inheritance pattern is autosomal recessive and atrophic scarring is absent. Molecular analysis of TNXB in a diagnostic setting is challenging. Abstract :